Audiovisual Media Effects on Poetic Imagery and Symbolic Depth in Bullying-Themed Poetry Writing: A Systematic Literature Review - Rozanna Ismarika; Hasan Busri; Dyah Werdiningsih (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
This systematic literature review aims to examine the effects of audiovisual media on poetic imagery and symbolic depth in bullying-themed poetry writing. Bullying remains a significant issue in educational settings, while poetry writing has emerged as a creative pedagogical tool that enables students to express their emotional experiences. However, the integration of audiovisual stimuli in poetry instruction remains underexplored, particularly regarding its impact on the quality of imagery and symbolism. This review analyzed 45 peer-reviewed articles published between 2015 and 2025, indexed in Scopus, Web of Science, and ERIC, following the PRISMA protocol. The findings identify three main thematic clusters. First, audiovisual media significantly enhance sensory imagery and figurative language in students’ poetry. Second, exposure to bullying-themed audiovisual content contributes to deeper symbolic meaning and greater metaphorical complexity. Third, multimodal pedagogical approaches promote emotional engagement and empathic perspective-taking, which in turn improve the overall literary quality of students’ poems. In addition, this review highlights several methodological gaps, particularly the limited number of longitudinal studies and the insufficient consideration of diverse cultural contexts. Based on these findings, a Multimodal Affective Symbolic (MAS) framework is proposed, integrating cognitive, affective, and semiotic dimensions. The implications for creative writing pedagogy and anti-bullying education are also discussed.